2015
DOI: 10.2106/jbjs.n.01033
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome and Glenoid Morphology After Arthroscopic Repair of Chronic Osseous Bankart Lesions

Abstract: Arthroscopic osseous Bankart repair is an effective primary treatment for shoulders with substantial glenoid bone loss as it provides successful outcomes without recurrence of instability once osseous union is obtained. Glenoid morphology can be normalized during the intermediate to long-term postoperative period, even in shoulders with a smaller fragment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 38 publications
0
64
0
3
Order By: Relevance
“… 45 The five- to eight-year follow-up study showed that after fixing a small fragment, the remnant defect was filled by the new bone formation and eventually the shape of the glenoid returned close to the original shape. 46 On the other hand, others reported that the smaller the fragment, the worse the union between the fragment and the glenoid, which in turn made the outcome worse. 44 At present, we recommend that the fragment be fixed to the glenoid if the reconstructed glenoid (native glenoid + bone fragment) is wide enough to cover the HSL (on-track lesion).…”
Section: Bony Bankart Lesionmentioning
confidence: 99%
“… 45 The five- to eight-year follow-up study showed that after fixing a small fragment, the remnant defect was filled by the new bone formation and eventually the shape of the glenoid returned close to the original shape. 46 On the other hand, others reported that the smaller the fragment, the worse the union between the fragment and the glenoid, which in turn made the outcome worse. 44 At present, we recommend that the fragment be fixed to the glenoid if the reconstructed glenoid (native glenoid + bone fragment) is wide enough to cover the HSL (on-track lesion).…”
Section: Bony Bankart Lesionmentioning
confidence: 99%
“…The rest of the patients demonstrated significant improvement of both the Rowe score 9 and the Western Ontario Shoulder Instability Index (WOSI) 10 postoperatively. In addition, they had substantial improvement in terms of glenoid bone loss (calculated as a percentage loss of the diameter of the assumed circle on the inferior aspect of the glenoid, not including the bone fragment, on a three-dimensional computed tomography [3D CT] image) to 21.1%, from 20.4% preoperatively, with the fragment size only 4.7% on average 1 . We believe that this substantial improvement of glenoid morphology was due to excellent fragment reduction and retensioning of the entire IGHL provided by the extensive labral release described above.…”
Section: Resultsmentioning
confidence: 99%
“…Hiroyuki Sugaya, MD 1 Norimasa Takahashi, MD 1 1 Shoulder & Elbow Center, Funabashi Orthopaedic Hospital, Hasama, Funabashi, Japan E-mail address for H. Sugaya: hsugaya@nifty.com E-mail address for N. Takahashi: n-h-taka@qc4.so-net.ne.jp…”
Section: Pitfalls and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Given the morbidity of Latarjet 10 and open Bankart 11,12 procedures, surgeons are well advised to adopt remplissage into their surgical armamentarium. In light of the work of Kitayama et al 13 showing bone hypertrophy after bony Bankart repair, I have begun adding local bone procured from the Hill-Sachs lesion to my capsulolabral reapproximation in addition to remplissage.…”
Section: See Related Article On Page 2894mentioning
confidence: 99%